Association between corneal hysteresis and the magnitude of intraocular pressure decrease after cataract surgery. Issue 6 (June 2015) - Deol, Madhvi; Ehrlich, Joshua R.; Shimmyo, Mitsugu; Radcliffe, Nathan M.
Abstract : Purpose : To evaluate the relationship between baseline corneal hysteresis (CH) and the change in intraocular pressure (IOP) before and after cataract extraction in patients without glaucoma. Setting : Private practice, New York City, New York, USA. Design : Retrospective cohort study. Methods : Charts of consecutive patients who had phacoemulsification cataract extraction with posterior chamber intraocular lens implantation were analyzed. All included patients had preoperative and postoperative measurements with the Ocular Response Analyzer 2 to 4 months and 10 to 12 months postoperatively. Data collected included age, baseline CH, baseline central corneal thickness (CCT), and IOP. Results : Thirty nine (65 eyes) of the 230 patients met the inclusion criteria. The mean patient age was 70.8 years ± 8.6 (SD). The mean preoperative, 2‐ to 4‐month and 10‐ to 12‐ month postoperative IOP values were 14.8 ± 3.5 mm Hg, 11.9 ± 3.4 mm Hg, and 12.6 ± 3.1 mm Hg, respectively ( P < .05 for comparisons with preoperative IOP). The baseline CH was not predictive of the IOP reduction at 2 to 4 months (β = −0.3; 95% confidence interval [CI], −0.7 to 0.01; P = .06). However, the baseline CH (but not the baseline CCT) was statistically associated with the magnitude of IOP reduction at 10 to 12 months when controlling for patient age (β = −0.5; 95% CI, −0.8 to −0.1; P = .01). Conclusion : A low baseline CH was associated with a larger magnitude of IOP reduction after cataract extraction. Financial Disclosure : Dr. Radcliffe is a consultant to Reichert Technologies and Glaukos Corp.; a consultant to and speaker for Allergan, Inc., Alcon Laboratories, Inc., Iridex Corp., Merge Healthcare, Carl Zeiss Meditec AG; and a speaker for Merck Pharmaceuticals. No other author has a financial or proprietary interest in any material or method mentioned.